THE EFFECT OF ENTREPRENEURSHIP LEARNING ON STUDENT ENTREPRENEURIAL DECISIONS - Isra Hayati; Susilawati Susilawati; Mutiah Khaira Sihotang (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine the Effect of Entrepreneurship Learning on Entrepreneurial Decisions of Students of the Faculty of Islamic Religion Muhammadiyah University of North Sumatra. The research method used in this study is a quantitative research method. The sample in this study were students of the Islamic Faculty of Muhammadiyah University of North Sumatra with a total of 89 students responding. Based on the results of the analysis, it shows that entrepreneurship learning can be seen from the tcount of 3,356 ttable 1,988 with a significant value of 0.001 0.05, this shows that the entrepreneurship learning variable influences interest in entrepreneurship, thus H1 is accepted.